Histone methyltransferase Smyd3 is a new regulator for vascular senescence. Issue 9 (11th August 2020) - Yang, Di; Wei, Gang; Long, Fen; Nie, Hongbo; Tian, Xiaoli; Qu, Lefeng; Wang, ShuangXi; Li, Peng; Qiu, Yue; Wang, Yang; Hong, Wanjin; Ni, Ting; et al.
Abstract: Endothelial cell senescence is one of the main risk factors contributing to vascular diseases. As increasing number of "epigenetic drugs" entering clinical trials, understanding the mechanism of epigenetic regulation in vascular aging has significant implications in finding targets to cure vascular diseases. However, the epigenetic regulation of endothelial senescence remains unclear. Based on the findings that increased protein level of histone H3 lysine 4 (H3K4) methyltransferase Smyd3 and elevated H3K4me3 modification happened in angiotensin II (Ang II)‐induced senescence in rat endothelial cells, we are curious about whether and how Smyd3 can regulate endothelial senescence. We found that an increase of Smyd3 alone promoted senescence‐associated phenotypes, while knockdown of Smyd3 blocked senescence in endothelial cells. Furthermore, Smyd3‐specific inhibitor reversed vascular senescence‐associated phenotypes at cellular level. Importantly, Ang II‐induced vascular senescence can be greatly alleviated in Smyd3 knockout (KO) mice and those treated with Smyd3 inhibitor. Mechanistically, Smyd3 directly bound to the promoter region of Cdkn1a (coding for p21), then caused its increased H3K4me3 level and elevated gene expression, and ultimately gave rise to senescence‐associated phenotypes. Intriguingly, Smyd3‐mediated p21 upregulated expression also exists in human tissues of vascular disease, indicating it is probably an evolutionarily conserved mechanism in regulating vascular senescence. Thus, Smyd3 can act as a novel factor regulating endothelial senescence through transcriptionally promoting p21 expression. Blocking the Smyd3‐p21 signaling axis may also have potential medical implications in treating diseases related to vascular aging. Abstract : Younger cell has lower levels of Smyd3 protein and H3K4me3 at the promoter region of p21 gene, with the result of low abundance of p21 protein. In endothelial senescence systems including Ang II‐induced RAECs, Ang II‐infused mice, replicative senescence, hypertensive rat model, and atherosclerotic human tissues, Smyd3 protein level was increased, leading to higher accumulation of H3K4me3 at the promoter of p21 gene, which further results in higher expression of p21, and finally causes senescence‐associated phenotypes.